Estudo quimico e das atividades biologicas dos alcaloides indolicos de Himatanthus lancifolius (Muell. Arg.) Woodson, Apocynaceae - (Agoniada) - Souza, Wesley Mauricio de, 1969- (2008)
Orientador : Prof. Tit. Cid Aimbire de M. Santos